Tafsir Methods of Certain Ayats al-Ahkam in Baydawi’s Work “Anwar al-tanzil wa asrar al-Ta'wil”(In the context of Purity and Worship) - Mustafayev, Anvar (Scholarya Demo Journal of Ruby, 2024)
Nasir al-Din Abu Said Abd Allah ibn Umar ibn Muhammad al-Baydawi’s famous tafsir work “Anwar al-tanzil wa asrar al-Ta'wil” is considered an outstanding example in terms of writing style. The scholar, who authored numerous works on Islamic sciences, possessed extensive scholarly knowledge. He was also well-known in disciplines such as fiqh and its methodology. In this regard, the scholar has demonstrated his ability in the interpretation of fiqh or ayats al-ahkam that cover topics such as worship, behavior, morality, halal, and haram. There are different opinions about the number of ayats al-ahkam, the meanings of which are clear to everyone and do not require interpretation or explanation.           Religious rites such as purity and worship are considered among the most important obligations that a man must fulfill before his Creator. The article addresses topics related to purification, such as ablution before divine service, ghusl, and tayammum, as well as, prayer which is considered to be the basis and pillar of the divine services, as interpreted in Baydawi’s tafsir from the ahkam ayats perspective. The research focused on the mufassir's interpretation of purity and worship, employing a descriptive style to develop the themes.            Baydawi, interpreting such ayats, followed the method and path established by the scholars of tafsir before him and preferred the Shafi’i madhab (school of thought) to which he belonged. As he presented the opinions and thoughts of other scholars and religious leaders on various issues encountered during his interpretation of ayats, the mufassir also took note of their supporting evidence. using verbs such as “qila” (was said) and “ruviya” (was told) in the passive voice.  Baydawi had not mentioned the names of those scholars or religious leaders while presenting their opinions and thoughts.) Furthermore, he cited examples from other ayats, along with important sources, such as hadith, ijma, and qiyas, to confirm his views in the interpretation of the mentioned ayats al-ahkam. Additionally, Baydawi enhanced his interpretation of the ayats by referencing the pronunciation of various religious leaders and imams.